Case Report: Sellar Ependymomas: A Clinic-Pathological Study and Literature Review - Zhao, Liyan; Jiang, Yining; Wang, Yubo; Bai, Yang; Liu, Liping; Li, Yunqian (Frontiers in Endocrinology, 2021)
Ependymomas are primary glial tumors arising from cells related to the ependymal lining of the ventricular system. They are classified into at least nine different molecular subtypes according to molecular phenotype, histological morphology, and tumor location. Primary sellar ependymoma is an extremely rare malignancy of the central nervous system, with only 12 known cases reported in humans. We herein report a case of ependymoma located at the pituitary region in a 44-year-old female patient and discuss the molecular subtype, natural history, clinical presentation, radiological findings, histological features, immunohistochemical characteristics, ultrastructural examinations, treatment, and prognosis of sellar ependymoma. This case report may serve as a helpful reference for clinicians and radiologists in clinical practice.